A novel and facile-to-synthesize three-dimensional honeycomb-like nano-Fe3O4@C composite: Electromagnetic wave absorption with wide bandwidth. (November 2020) - Deng, Yunfei; Zheng, Yun; Zhang, Danfeng; Han, Congai; Cheng, Ao; Shen, Junyao; Zeng, Guoxun; Zhang, Haiyan
Abstract: The three-dimensional honeycomb-like nano-Fe3 O4 @C (HcFe3 O4 @C) composite and the three-dimensional honeycomb-like porous carbon (HcC) were prepared through a two-step colloidal template method. The HcFe3 O4 @C composite material shows a three-dimensional multilayer honeycomb-like structure with a uniform pore diameter of 100 nm, while the HcFe3O4@C composite exhibits enhanced absorbing properties with a low Fe3O4 content(28.95%).HcFe3 O4 @C composite display an optimal reflection loss (RL) value of −46.4 dB at 9.6 GHz at a thin thickness of 3.5 mm, and a wide absorption bandwidth of 5.04 GHz. These enhanced EM wave absorption performances are attributed to the synergistic effects of Fe3 O4 and carbon as well as the structural advantages, such as multiple reflections of electromagnetic waves in the three-dimensional honeycomb structure and interface polarization caused by Fe3 O4 nanoparticles and carbon layer. The work herein reported provides a new route for preparing ferrite-carbon based absorbers with honeycomb-like nanostructures. Graphical abstract: The three-dimensional honeycomb-like nano-Fe3 O4 @C composite material prepared by the two-step method of colloidal crystal template shows excellent electromagnetic wave performance through strong dielectric loss, magnetic loss and multiple reflections of incident electromagnetic waves. Image 1